Contribución en el análisis y simulación de una red MPLS con la Internet de los servicios diferenciados DIFFSERV - Bustamante Alvarez, Rafael (2007)
-- The advent of Internet and the globalization have modified the forms of communication in the world and the enterprises. All this has brought the search of facilities of communications permanents and secures with quality of service to improve the Internet The studies of the news networks with MPLS are in a process that consists in finding news focus to improve the quality of service and rerouting. This thesis consists in analyzing and simulates MPLS with DiffServ to demonstrate that the use of the L-LSP is a good solution to improve the throughput in the network. The other side, it proposes a new method for updating time to rerouting in the network uses OSPF. Finally, it does an analysis and simulation of the network behavior, in case of the fail a link. It is to say the resilence of the network.